2022
DOI: 10.1088/1402-4896/ac95d8
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the structural, optoelectronic, dynamical stability and transport properties of Boron-doped CaTiO3: DFT based study

Abstract: Undoped and B-doped CaTiO3 Semiconductor Perovskite is investigated by the Density Functional Theory (DFT) and Boltzman transport theory (BoltzTraP) using full potential linearized augmented plane wave (FP-LAPW) method with GGA-PBE approximation. By incorporating B into CaTiO3, the electrical band gap is effectively reduced, and adjusting the substitution atom type may regulate the degree of band gap reduction. As a result, the visible light absorption ability is increased. Our results indicate that all doped … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…Hereby, the DRS data obviously shows that the synergistic effect of both B and GO loading in CaTiO 3 bricks increases the absorption of the visible range by the catalysts and accordingly the photocatalytic activity was also improved. Attou et al [49] investigated the band gaps of undoped and B-doped CaTiO 3 semiconductor perovskites with Density Functional Theory (DFT) and Boltzman transport theory (BoltzTraP) using the full potential linearized augmented plane wave (FP-LAPW) method with the GGA-PBE approach. They stated that by incorporating B into CaTiO 3 , the band gap efficiently decreased and as a result, the ability to absorb visible light increased.…”
Section: Structural and Morphological Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Hereby, the DRS data obviously shows that the synergistic effect of both B and GO loading in CaTiO 3 bricks increases the absorption of the visible range by the catalysts and accordingly the photocatalytic activity was also improved. Attou et al [49] investigated the band gaps of undoped and B-doped CaTiO 3 semiconductor perovskites with Density Functional Theory (DFT) and Boltzman transport theory (BoltzTraP) using the full potential linearized augmented plane wave (FP-LAPW) method with the GGA-PBE approach. They stated that by incorporating B into CaTiO 3 , the band gap efficiently decreased and as a result, the ability to absorb visible light increased.…”
Section: Structural and Morphological Analysismentioning
confidence: 99%
“…was also improved. Attou et al [49] investigated the band gaps of undoped and B-doped CaTiO3 semiconductor perovskites with Density Functional Theory (DFT) and Boltzman transport theory (BoltzTraP) using the full potential linearized augmented plane wave (FP-LAPW) method with the GGA-PBE approach. They stated that by incorporating B into CaTiO3, the band gap efficiently decreased and as a result, the ability to absorb visible light increased.…”
Section: Structural and Morphological Analysismentioning
confidence: 99%
“…First-principles calculations have also provided theoretical support for the proposition that substitutional N doping at O sites introduces impurity states within the band gap [23]. In addition, Attou et al [24] conducted density functional theory (DFT) calculations to investigate the doping effect by replacing oxygen sites in CaTiO 3 with boron(B) revealing that the appearance of the p energy level of dopants leads to a narrowed band gap and enhanced response to visible light.…”
Section: Introductionmentioning
confidence: 99%
“…As an emerging high-temperature oxide TE material, there is a limited body of experimental research available on the TE properties of CaTiO 3 . The reported TE properties of pristine CaTiO 3 are mainly obtained through theoretical calculations. Attou et al predicted that the zT value of B-doped CaTiO 3 (B@Ca) can reach 0.56 at 800 K . Bak et al observed a n-p type transformation in the Seebeck coefficient of CaTiO 3 at high temperatures (1173–1323 K) under different oxygen partial pressures. , It indicates that the presence of oxygen vacancies can lead to an n -type conduction behavior.…”
Section: Introductionmentioning
confidence: 99%